Politics from Below: Protest, Violence and Social Justice in the City of Shiraz, 1835-1848 - Aharonov, Moshe (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2010)
This article analyzes the dynamic relationship between the inhabitants of the city of Shiraz, mainly taxpayers and marginal elements, on the one hand, and government authorities, on the other hand, during the reign of Muhammad Shah (1835-1848). It seeks to uncover the mechanisms which the city’s inhabitants used in order to promote their goals and impose their rooted cultural codes, flagrantly broken by the ruling elites. First, the article discusses the social networks and the mechanisms of recruitment for political action in Shiraz, and then it offers an analysis of the political and socio-economic life in southern Iran. Ultimately, the article examines political protest and urban politics as initiated from below, that is by the local population, focusing on the people of the bazaar and on elements in the margins of society. It shows that despite the lack of urban formal political institutions and class consciousness, as well as the dependency on local notables, taxpayers in Shiraz were not ‘inevitable victims’ of the political and social systems in the city. In many cases, especially in times of hardship and severe injustice, they were able to negotiate with the city authorities and speak out clearly. They took advantage of the ongoing internal conflicts between members of ruling elites, the fragility of the weak regime in Tehran and the dynasty’s ethos to ensure peace and stability. They managed to disengage from elite politics and to participate in politics from below in order to promote social justice and moral economy.